Peran Muhammadiyah Dalam Dinamika Politik Bangsa Indonesia Kontemporer: Antara Khittah, Ijtihad Politik, Dan Kontribusi Kebangsaan - Yoanda Eka Putera; Yugo Widya Iratama; Mardiana Dina (Ameena Journal, 2026)
This study examines Muhammadiyah's role in Indonesia's contemporary political dynamics, focusing on three main dimensions: the khittah (ideological guideline), political ijtihad as an adaptation mechanism, and national contribution as a manifestation of civic engagement. Using library research with a qualitative-descriptive approach, this study analyzes official Muhammadiyah documents, academic works, and relevant policy reports. The findings indicate that Muhammadiyah has successfully maintained its identity as a socio-religious movement (civil Islam) while responding to political issues affecting the community and the nation. Although not formally affiliated with any political party, Muhammadiyah actively participates in democratic processes through policy advocacy, civic education, and civil society empowerment. This study concludes that Muhammadiyah's model of ethical-critical political engagement represents a unique contribution to democratic consolidation in Indonesia.